Efektivitas Akupresur Titik P⁶ dan ST³⁶ serta Relaksasi Napas Dalam terhadap Postoperative Nausea and Vomiting pada Pasien Sectio Caesarea - Brilliant, Fannia Zata; Yuliwar, Roni (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Postoperative Nausea and Vomiting (PONV) is a common complication after Sectio Caesarea (SC) that causes discomfort and slows recovery. Acupressure and deep breathing relaxation are non-pharmacological therapies to reduce PONV. The purpose of this study was to determine the effectiveness of acupressure at points P⁶ and ST³⁶ and deep breathing relaxation on reducing PONV intensity in SC patients. The research design used was a quasi-experimental with a Two Group Pre-Test and Post-Test Design. A sample of 64 research subjects was divided into two groups. PONV intensity was measured using the RINVR scale. Data analysis used Paired Sample T-Test and Independent Sample T-Test. The results showed that the average PONV before treatment in the first group was 14.44 and after 7.34 (p < 0.05). The average before treatment in the second group was 14.63 and after 9.38 (p < 0.05). There was a significant difference in effectiveness between the two groups (p < 0.05), the first group treatment was more effective in reducing PONV. In conclusion, acupressure of the P⁶ and ST³⁶ points is more effective than deep breathing relaxation in reducing the intensity of PONV in SC patients.